The law of the single price within one country: the example of Benin - N.C.C. Vikou (Вестник университета)
This article aims to test the hypothesis of the law of the single price within one country on the example of the regions of Benin. The checking of the hypothesis was carried out empirically and is based on unit root tests for panel data on consumer prices at the national level of Benin. Special attention is paid to the review of the most relevant unit root tests used for the analysis of the Panel data. The study noted how a shock affecting prices in one region could also affect prices in other regions of the country, due to cross-dependence. The time series of consumer prices by regions of Benin were used. A technique has been proposed that takes into account the possibilities of studying the cross-dependence of the data and defines the conditions for selecting the unit root test to verify the implementation of the law of the single price. As a result of the analysis of the stationarity of panel data, it was found that the law of a single price is not observed for all essential goods in the regions of Benin and an assessment of the differentiation of the country’s regions by the level of consumer prices was obtained.